2017
DOI: 10.1515/iss-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Surgical data science: the new knowledge domain

Abstract: Healthcare in general, and surgery/interventional care in particular, is evolving through rapid advances in technology and increasing complexity of care with the goal of maximizing quality and value of care. While innovations in diagnostic and therapeutic technologies have driven past improvements in quality of surgical care, future transformation in care will be enabled by data. Conventional methodologies, such as registry studies, are limited in their scope for discovery and research, extent and complexity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 98 publications
0
34
0
Order By: Relevance
“…An essential component of the control tower is the datadriven modeling and understanding of the clinical activities, an undertaking that taps into the emerging research field of Surgical Data Science [3], [4]. Machine learning has been key to generate models of procedural interventions from data [139], [140] and ontologies have also been developed to standardize the resulting models [141].…”
Section: B An Endeavour Rooted In Surgical Data Sciencementioning
confidence: 99%
“…An essential component of the control tower is the datadriven modeling and understanding of the clinical activities, an undertaking that taps into the emerging research field of Surgical Data Science [3], [4]. Machine learning has been key to generate models of procedural interventions from data [139], [140] and ontologies have also been developed to standardize the resulting models [141].…”
Section: B An Endeavour Rooted In Surgical Data Sciencementioning
confidence: 99%
“…Focusing only on one specialization, psychotherapy, Miner and colleagues [16] outlined four approaches and dimensions of care that conversational AI will affect when integrated into mental health service delivery. Focusing on surgery and surgical data science (SDS), Vedula and Hager [26] suggested that SDS could transform passive surgical technologies into an interactive platform that can collaborate with and actively assist physicians. Motivated by the "black box" problem in AI techniques, Lai and colleagues [13] reviewed research on CDSS with respect to the role of explanations.…”
Section: Related Workmentioning
confidence: 99%
“…In this issue, the theoretical background of Surgery 4.0 is outlined by Vedula and Hager [2] in their paper “Surgical data science: the new knowledge domain”. They posited compellingly that future transformation in surgical care will be driven by data/information.…”
Section: Surgery and The 40 Developmentmentioning
confidence: 99%